Is there a correlation between depressive symptoms and motor skills in post-stroke patients? - Hélio Mamoru Yoshida; Fabrício Oliveira Lima; Júlia Barreira; Simone Appenzeller; Paula Teixeira Fernandes (Arquivos de Neuro-Psiquiatria)
ABSTRACT Deficits in motor skills and depressive symptoms are common effects observed after stroke, so it is necessary to understand how these variables interact with each other. Therefore, the aim of this study was to investigate the relationship between these two variables in post-ischemic stroke patients. We evaluated 135 patients with a mean age of 60 years (± 15). The Fugl-Meyer assessment of motor function was used to assess motor skills in the upper limbs, lower limbs, balance, and sensitivity and the Beck Depression Inventory was applied to evaluate depressive symptoms. To assess the relationship between both components, Spearman's correlation was performed. Depressive symptoms were negatively correlated with all variables of motor skills. This study suggests that higher motor skills in post-stroke patients may be associated with fewer depressive symptoms. Thus, a better understanding of how post-stroke symptoms are interrelated may improve patient treatment and care, contributing to a better quality of life.